Pengaruh Implementasi Sistem Informasi Manajemen Terhadap Kualitas Pengambilan Keputusan Strategis dan Dampaknya Terhadap Kinerja Organisasi - Safira, Muthia; Putri, Tri Anada (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the effect of the implementation of Management Information Systems (MIS) on the quality of strategic decision-making and its impact on organizational performance. The research uses a quantitative approach with an explanatory research method. Data were collected through a survey of 120 respondents consisting of managers and staff in organizations that have implemented MIS for at least two years. The analysis techniques used include validity and reliability tests, multiple linear regression, as well as mediation tests using the Sobel Test method. The research results show that system quality, information quality, and top management support have a significant effect on the quality of strategic decision-making. Decision quality has been proven to have a significant impact on organizational performance and mediates the relationship between MIS implementation and organizational performance. These findings reinforce DeLone & McLean's theory as well as the Resource-Based View that information management is a strategic organizational resource.